From Collectives to Connectives: Italian Media Activism and the Repurposing of the Social - Alessandra Renzi (University of Toronto, 2011)
The dissertation develops the concept of repurposing as a means for thinking with activists and the issues they confront. It moves alongside pirate television collective insu^tv as they draw on a variety of histories, traditions and technological resources for their practices. Repurposing functions on multiple levels and at multiple scales, from the recycling of materials and spaces to the harnessing and relaying of encounters and events within an ever-expanding field of social relations. When seen as a way of connecting activist groups and communities, the repurposing of media contributes to strengthening an often fragmented and conflicted activist field. Indeed, insu^tv's use of information and technology brings to the fore the value of media activism for the creation of social assemblages in which the “media” literally mediates between individuals and among individuals and their environment, instituting and developing an ontogenetic relation (Simondon, 1989). Yet, rather than simply making sense of insu^tv's practices, the concept of repurposing also provokes a discussion regarding the ethics of connection. For insu^tv, this connective ethics can be understood as a set of rules and principles that facilitate the evaluation of actions, communication, and thought according to an immanent mode of collective existence (Deleuze, 1988; Simondon, 1989). For the author, herself a member of insu^tv and an academic researcher, this immanent position helps challenge traditional models of knowing and envisioning social change and instead proposes alternatives that attend to the singularity and relation among new political movements, and to the political potential of research methods that focus on process and fold activism into academia. The methodology is inspired by the militant research methods of the Italian Autonomia movement (conricerca or inchiesta), as developed and performed by activists themselves. While attending to the complexity of social struggles, the concept of repurposing enables an approach to research and experimentation as modes of sociability, where these modes are themselves repurposed through an ethics of connection. This line informs the relation between ethics and subjectivation, as well as between ethics and micropolitics, facilitating the emergence of new modes of political action through the repurposing of the social field itself.
hdl:1807/29845
Keywords: P16; Z1; L82; 330; activism; autonomy; differential accumulation; grassroots media; Italy; Telestreet